Μετάφραση από τα αγγλικά στα ελληνικά και σχολιασμός του άρθρου Age-related muscle atrophy in the lower extremities and daily physical activity in elderly women. - (:unkn) unknown (My University, 2023)
Η παρούσα πτυχιακή εργασία, η οποία συντάχθηκε με βάση τον κανονισμό εκπόνησης πτυχιακής εργασίας του Τμήματος Ξένων Γλωσσών, Μετάφρασης και Διερμηνείας (ΤΞΓΜΔ) του Ιονίου Πανεπιστημίου, σηματοδοτεί την ολοκλήρωση των σπουδών μου στην κατεύθυνση της μετάφρασης στο ΤΞΓΜΔ. Στην περίπτωσή μου, η εργασία αφορά την μετάφραση και τον σχολιασμό ενός άρθρου που κατατάσσεται στον τομέα της ιατρικής, από τα αγγλικά στα ελληνικά με τίτλο Age-related muscle atrophy in the lower extremities and daily physical activity in elderly women (Η σχετιζόμενη με την ηλικία μυϊκή ατροφία στα κάτω άκρα και η καθημερινή σωματική δραστηριότητα σε ηλικιωμένες γυναίκες). Στο θεωρητικό μέρος δίνεται εν συντομία ο ορισμός της μετάφρασης και συγκεκριμένα η διάκρισή της σε γενική και τεχνική. Στην συνέχεια παρατίθεται το κυρίως μέρος, δηλαδή το πρακτικό κομμάτι της εργασίας, το οποίο αποτελείται από τρία μέρη: το μεταφρασμένο κείμενο, τον σχολιασμό και το γλωσσάρι ορολογίας, το οποίο παρατίθεται ως παράρτημα. Ακόμη, κλείνοντας, παρατίθενται τα συμπεράσματα και τέλος τα παραρτήματα, δηλαδή το πρωτότυπο κείμενο και το γλωσσάρι ορολογίας.

The following graduate thesis, which was completed based on the instructions of the Department of Foreign Languages, Translation, and Interpreting (DFLTI) of the Ionian University and marks the completion of my studies in translation. In this case, the thesis has to do with the translation and commentary of a medical article from English to Greek about the Age-related muscle atrophy in the lower extremities and daily physical activity in elderly women. lower limbs and daily physical activity in older women. To begin with the theoretical part, the definition of translation is briefly given, and specifically its distinction between general and medical translation. Secondly, the main part is listed as the practical part of the thesis, which is consisted of three parts: translated text, commentary, and the glossary of terms, which is listed as an appendix. In the end, we have the conclusions and finally the appendices that were used for the thesis, such as the original text and the glossary of terms.
Translation from English to Greek and commentary on the article Age-related muscle atrophy in the lower extremities and daily physical activity in elderly women
Keywords: ιατρική μετάφραση, σχολιασμός, μυϊκή ατροφία; medical translation, commentary, muscle atrophy